Antioxidant, thrombolytic, analgesic, and central nervous system depressant effects of Uvaria ferruginea leaf extracts: in-vitro, in-vivo, and in-silico approaches for potential drug discovery - Jinat Fatema, Sharna; Halima, Akter; Md. Anamul, Haque; Kaniz, Fatema; Md. Najem, Uddin; Mohsin, Kazi; Rezaur, Rahman; Md. Zahidul, Islam; Md Abdul Majed, Patwary (Elsevier B.V., 2025)
Uvaria ferruginea is a shrub of the Annonaceae family. Most of the species of Uvaria have been used as ethnomedicine. The present investigation examines the antioxidant, thrombolytic, analgesic, and CNS-depressant properties of U. ferruginea leaf extracts. DPPH, ferric reducing power, and phospho‑molybdenum tests were conducted to assess antioxidant potential, while in vitro clot lysis was used to detect the thrombolytic effect. Analgesic (acetic acid-induced writhing and tail immersion tests) and CNS-depressant (open-field and hole cross tests) effects were evaluated on the mice model. Phenolic (954.2 ± 14.2, 667.02 ± 11.4, and 624.4 ± 12.5 mg/g gallic acid, respectively) and flavonoid (746.5 ± 14.40, 625.8 ± 12.3, and 556.8 ± 12.3 mg/g quercetin equivalent) compounds were highly present in water (WUFL), ethyl acetate (EUFL) fractions, and methanol (MUFL) extract. Therefore, they showed a prominent antioxidant capacity in phospho‑molybdenum (963.63 ± 12.4, 700.00 ± 8.2 and 581.8 ± 12.2 mg/g equivalent of ascorbic acid), DPPH (42.35% – 80.68 %, 35.26 % - 76.32 % and 26.35 % - 69.42 % inhibition and 14.17 ± 1.3, 28.22 ± 1.9 and 67.16 ± 3.86 μg/mL IC50 values) and ferric reducing power (EC50: 25.11 ± 3.44, 35.63 ± 4.09 and 41.30 ± 2.90 μg/mL) tests. Similarly, WUFL (74.17 ± 2.92 %), followed by EUFL (68.56 ± 0.54 %), showed significant (p*** < 0.001) thrombolytic activity. Besides, WUFL showed 81.23 % inhibition of abdominal writhing and significantly (p*** < 0.001) increased (11.38 ± 0.09 s) the response time in hotplate tests. Moreover, WUFL, EUFL, and MUFL showed a prominent CNS-depressant effect in an open field (88.77, 83.23, and 74.29 % inhibition of movement, respectively) and hole cross (82.19, 79.04, and 62.30 % inhibition of locomotion, respectively) tests at a 200 mg/kg dose. Meanwhile, an acute toxicity study showed no toxicity up to a 2000 mg/kg dose. The GC–MS analysis revealed 11 prominent phytochemicals in the methanol extract whereas, in-silico studies have proved that some compounds like sesquiterpene alcohol (C2) have strong binding energy (−8.5, −7.4, −8.1 and − 7.2 kcal/mol) with antioxidant (6NGJ), thrombolytic (1A5H), analgesic (5F1A), and CNS-depressant (4COF) proteins respectively. ADMET results showed excellent absorption and noncarcinogenic properties, while PASS prediction endorsed their aforementioned properties. In conclusion, the plant has prominent bioactive compounds with potential antioxidant, thrombolytic, analgesic, and CNS-depressant effects. In the future, these compounds can be isolated for study as lead compounds in new drug discovery, and the leaf can be used as herbal medicine.